Therapeutic effects of Crataegus monogyna inhibitors against breast cancer - Basavarajappa, Girish Meravanige; Rehman, Abdur; Shiroorkar, Predeepkumar Narayanappa; Sreeharsha, Nagaraja; Anwer, Md. Khalid; Aloufi, Bandar (Frontiers in Pharmacology, 2023)
Breast cancer is a silent killer disorder among women and a serious economic burden in health care management. Every 19 seconds, a woman is diagnosed with breast cancer, and every 74 seconds, a woman worldwide passes away from the disease. Despite the pop-up of progressive research, advanced treatment approaches, and preventive measures, breast cancer remains amplifying ailment. This study provides a mixture of data mining, network pharmacology and docking analysis which would surely revolutionize cancer treatment by exploitation of prestigious phytochemicals. Crataegus monogyna is a small, rounded deciduous tree with glossy, deeply lobed leaves and flat sprays of cream flowers, followed by dark red berries in autumn. Various stduies demonstrated that C. monogyna is therapeutically effective against breast cancer. However, the particular molecular mechanism is still unknown. This study is credited for locating bioactive substances, metabolic pathways, and target genes for breast cancer treatment. According to the current investigation, the bioactive compounds of C. monogyna may operate as a viable solution against breast cancer by altering the target genes implicated in the disease pathogenesis, which examined compound-target genes-pathway networks. The expression level of target genes was analyzed using GSE36295 microarray data. Further, docking analysis and molecular dynamic simulation studies strengthened the current findings by validating the effective activity of the bioactive compounds against putative target genes. In summary, we propose that six key compounds, luteolin, apigenin, quercetin, kaempferol, ursolic acid, and oleanolic acid contributed to the development of breast cancer by affecting MMP9 and PPARG proteins. Integration of network pharmacology and bioinformatics revealed C. monogyna's multi-target pharmacological mechanisms against breast cancer. This study provides convincing evidence that C. monogyna might partially alleviate the breast cancer and ultimately lays a foundation for further experimental research on the anti-breast cancer activity of C. monogyna.